Теоретическая модель поляротаксиса - Францевич, Л.И. (Вестник зоологии, 1979)
The model affords a possibility to navigate by polarized light by means of comparing the observed pattern of sky polarization with a standard one. The standard pattern could be built into the structure of a compound eye. The standard (or null) direction of polarization in every model ommatidion coincides with the position of microvilli in a polarization-sensitive photoreceptor. The angle between the observed and null direction of polarization at each point of the visual field serves as an estimate of the error angle of the body axis relative to the solar position. Some standards are considered together with the errors of orientation by a single sky area or by averaged deviation signals. The results predicted by the model are compared to the cited experimental data.